Book Review: Gra jako obiekt oporny. Performatywność w relacji gracza i gry cyfrowej by Justyna Janik - Chojnacki, Marcin M. (Replay. The Polish Journal of Game Studies, 2023)
Justyna Janik’s book takes up the topic of the materiality of video games and proposes analyzing it using a posthumanist perspective. The Author introduces the concepts of intra-action (Karen Barad) and bio-object (Tadeusz Kantor), which she uses as tools to describe the specificity of the relationship between humans and video games, which is a form of constant communication and sharing of agency between the player and the simulation elements. Janik’s book is an interesting study of the autonomy of the game object and the resistance it manifests. This provides an inspiring basis for reflection on the materiality of software, the occurrence of glitches, the preservation of games, the technical background of the game, and the traces left by other players.